Genome-wide DNA methylation profiling and its involved molecular pathways from one individual with thyroid malignant/benign tumor and hyperplasia: A case report. Issue 35 (August 2016) - Cai, Liang-Liang; Liu, Guo-Yan; Tzeng, Chi-Meng
Abstract: Background: During development, methylation permanently changes gene activity, while aberrant gene methylation is key to human tumorigenesis. Gene methylation is an epigenetic event leading to gene silencing and some tumor suppressor genes that are aberrantly methylated in both thyroid cancer and benign thyroid tumor, suggesting a role for methylation in early thyroid tumorigenesis. Specific gene methylation occurs in certain types of thyroid cancer and depends on particular signaling pathways. Most reports rely on data from varied samples that vary tremendously with respect to methylation. Results: We observed that hyperplastic/malignant (H/M) thyroid tissue and benign/manligant (B/M) tissue had the most profoundly methylated loci compared to hyperplastic/benign (H/B) tissue. These loci are mapped to 863 genes (|Δβ value| > 0.15) in B/M and 1082 genes (|Δβ value| > 0.15) in H/M. After bioinformatic analysis, these genes were found to be involved in T-cell receptor signaling pathway (B/M) and Jak–Stat signaling pathways (H/M). Conclusion: Our study offers the most comprehensive DNA methylation data for thyroid disease to date, using 1 patient with 3 tissue types and high-resolution 450K arrays. Our data may lay the foundation for future identification of novel epigenetic targets or diagnosis of thyroid cancer. Abstract : Supplemental Digital Content is available in the text